Incidence and predictors of worsening heart failure in patients with wild‐type transthyretin cardiac amyloidosis. (22nd June 2022) - Ladefoged, Bertil Thyrsted; Dybro, Anne; Dahl Pedersen, Anders Lehmann; Rasmussen, Torsten Bloch; Vase, Henrik Ølholm; Clemmensen, Tor Skibsted; Gillmore, Julian; Poulsen, Steen Hvitfeldt
Abstract: Background: Prognostic markers of survival have been identified in wild‐type transthyretin amyloidosis (ATTRwt), but limited data exist with respect to hospitalizations with worsening heart failure (WHF). Predictive markers of WHF have yet to be identified. Methods: From April 2017 to February 2021, 104 patients with ATTRwt were diagnosed and prospectively followed from the time of diagnosis to the time of death or the censoring date of 1 February 2021. Baseline patient characteristics, biomarkers, and advanced echocardiography were used to predict hospitalization with WHF. Results: During the median follow‐up period of 23 months, 51% of patients were hospitalized due to WHF. Seventy‐three per cent of patients with WHF were admitted at least twice. Patients with WHF during the first year had significantly poorer survival ( P  < 0.001). Independent predictors of WHF during follow‐up were pacemaker implantation prior to diagnosis (PMI, P  = 0.037) and right atrial volume index (RAVi, P  = 0.008). Patients with PMI had a higher left ventricular mass index and poorer left ventricular and right ventricular systolic function indicating a more advanced stage of amyloid disease. Conclusions: A high incidence and recurrence of hospital admissions with WHF were demonstrated in contemporary patients with ATTRwt, which was associated with reduced survival. Patients with pacemaker devices prior to ATTRwt diagnosis experienced more frequent hospitalizations with WHF. PMI and right atrial enlargement were identified as independent predictors of WHF during follow‐up.